Multiscale and age‐dependent leaf nickel in the Ni‐hyperaccumulator Leptoplax emarginata. Issue 4 (24th March 2018) - Bartoli, François; Royer, Mathilde; Coinchelin, David; Le Thiec, Didier; Rose, Christophe; Robin, Christophe; Echevarria, Guillaume
Abstract: Nickel‐hyperaccumulator plants are of interest due to their potential use in agromining. We aimed to characterize leaf traits and Ni concentration variabilities occurring between individual plants, leaves of differing age or between various leaf tissues, in a single Greek population of the Ni‐hyperaccumulator Leptoplax emarginata (Boiss.) O.E. Schulz. We linked these results to ecophysiological characteristics and other element concentrations at leaf and leaf tissue scales. We measured leaf gas exchanges, stomatal density, and we carried out rapid freezing and freeze‐drying processes on leaf sections before microanalysis with scanning electron microscopy and energy‐dispersive spectrometry. Leaf or leaf‐tissue Ni concentrations were influenced by a combination of individual plant and leaf age factors. The greatest Ni concentrations were found in the highly transpiring young and thin leaves with the greatest stomatal densities. Indeed, Ni was statistically seven times more concentrated in both epidermis layers than in their bulk neighbour leaf counterparts, whatever the leaf age. In both epidermis layers, increases in the Ni–S and Mg–S correlations from the oldest leaves to the youngest ones were observed. The Mg:Ni, Ca:Ni and P:Ni mass ratios decreased from the oldest leaves to the mature leaves. We would recommend time‐series characterization of leaf traits belonging to at least three plant replicates in order to take into account the allogamous character of many Ni‐hyperaccumulator plants. Long‐distance Ni transport via the xylem is predominant in the Ni‐hyperaccumulator L. emarginata whereas a complementary redistribution via the phloem should also occur. The perspectives of this study are the validation and refinement of this process over shorter periods using relevant tracers.